2013
DOI: 10.1093/bioinformatics/btt240
|View full text |Cite
|
Sign up to set email alerts
|

A context-sensitive framework for the analysis of human signalling pathways in molecular interaction networks

Abstract: Motivation: A major challenge in systems biology is to reveal the cellular pathways that give rise to specific phenotypes and behaviours. Current techniques often rely on a network representation of molecular interactions, where each node represents a protein or a gene and each interaction is assigned a single static score. However, the use of single interaction scores fails to capture the tendency of proteins to favour different partners under distinct cellular conditions.Results: Here, we propose a novel con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Our own work (29,34) and that of other groups (3537) demonstrated that the addition of functional and tissue-expression data, in combination with basic graph algorithms, enables the construction of PPI networks that are highly relevant to a specific research question. In particular, we showed that when cellular signaling is studied in an infectious or genetic disease context, combining both gene expression information from the tissue affected by the disease and predicted network information flow, serves to highlight important mediators of disease from the PPI hairball surrounding the studied proteins (29).…”
Section: Resultsmentioning
confidence: 94%
“…Our own work (29,34) and that of other groups (3537) demonstrated that the addition of functional and tissue-expression data, in combination with basic graph algorithms, enables the construction of PPI networks that are highly relevant to a specific research question. In particular, we showed that when cellular signaling is studied in an infectious or genetic disease context, combining both gene expression information from the tissue affected by the disease and predicted network information flow, serves to highlight important mediators of disease from the PPI hairball surrounding the studied proteins (29).…”
Section: Resultsmentioning
confidence: 94%
“…Another group created a framework for assigning context-sensitive weights to protein-protein interaction data [41]. Their method is based on the idea that proteins have preferred interaction partners depending on the cellular context.…”
Section: Gene Set Definitionsmentioning
confidence: 99%
“…Their method is based on the idea that proteins have preferred interaction partners depending on the cellular context. Applying this framework to identify pathways activated during influenza infection, they found that high-scoring context-sensitive paths in a PPI network were more likely to include biologically relevant proteins (those shown to have a significant effect on viral propagation and interferon production when silenced in an siRNA experiment) [41]. …”
Section: Gene Set Definitionsmentioning
confidence: 99%
“…Very few proteins perform their functions alone. Instead, most proteins function by interacting with others to form complexes and/or protein-protein interaction (PPI) networks [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. To understand PPIs at structure level, their 3D structures may be needed.…”
Section: Introductionmentioning
confidence: 99%